2000
DOI: 10.1038/sj.jhh.1000935
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-1-antitrypsin phenotypes in patients with renal arterial fibromuscular dysplasia

Abstract: Fibromuscular dysplasia (FMD) is a significant cause of renal artery stenosis, especially in young females. A rare association between FMD and ␣ 1 -antitrypsin (␣ 1 -AT) deficiency has been reported. We compared the ␣ 1 -AT phenotype distribution in 83 patients with renal arterial FMD with those published for Australian populations. ␣ 1 -AT phenotyping was performed by isoelectric focusing between pH 4.2 and pH 4.9 on polyacrylamide gels with PiM1M2, PiFM (non-deficiency alleles), PiMS and PiMZ (deficiency all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…FMD is an uncommon arterial disease, the cause of which remains unknown. A role for genetics in the pathogenesis is supported by a number of studies identifying FMD in family members, [8][9][10][11][12][13][17][18][19] association of FMD with a variety of genetic abnormalities, 7,[20][21][22][23][24] and the coexistence of FMD with Mendelian vascular connective tissue disorders. [25][26][27] Patients with FMD and a clinical phenotype consistent with these disorders may be referred for genetic counseling and eventual testing; however, the diagnostic yield of genetic testing for Mendelian connective tissue disorders in this population has not been determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FMD is an uncommon arterial disease, the cause of which remains unknown. A role for genetics in the pathogenesis is supported by a number of studies identifying FMD in family members, [8][9][10][11][12][13][17][18][19] association of FMD with a variety of genetic abnormalities, 7,[20][21][22][23][24] and the coexistence of FMD with Mendelian vascular connective tissue disorders. [25][26][27] Patients with FMD and a clinical phenotype consistent with these disorders may be referred for genetic counseling and eventual testing; however, the diagnostic yield of genetic testing for Mendelian connective tissue disorders in this population has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of reports connecting FMD with α 1 -antitrypsin deficiency. [20][21][22][23] In addition, a single study found that FMD patients had a significantly higher frequency of the angiotensin-converting enzyme (ACE) I allele, which has been associated with decreased levels of circulating ACE. 24 Finally, Sang and colleagues found a higher prevalence of the class II human lymphocytic antigen (HLA)-DRw6 in patients with FMD compared to control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…1 Studies have explored the potential relationship between FMD and genetic connective tissue disorders that can present with vascular manifestations, such as Loeys-Dietz, Marfan, and Ehlers-Danlos syndromes, and isolated case reports have noted concomitant FMD lesions in patients with these classical genetic disorders. [25][26][27][28][29][30][31] In a series of patients with FMD from Cleveland Clinic who underwent genetic testing for selected connective tissue disorders, including Ehlers-Danlos syndrome and Loeys-Dietz syndrome, the overall yield of these tests was low. 31 These studies suggest some overlap of FMD and other vascular connective tissue disorders, as well as the likelihood that the arterial manifestations of FMD may develop through multiple potential genetic pathways.…”
Section: Fmd and Connective Tissue Featuresmentioning
confidence: 99%
“…6 However, low AAT plasma levels were recently found in a study of 22 Spanish patients with sCAD. 8 Because AAT deficiency is a relatively frequent condition, the finding of deficiency alleles in some patients with sCAD may be accidental. 8 Because AAT deficiency is a relatively frequent condition, the finding of deficiency alleles in some patients with sCAD may be accidental.…”
Section: Resultsmentioning
confidence: 99%